Longitudinal relationship between internet self-control and problematic internet use among Chinese adolescents: mediating role of meaning in life - Wang, Weijun; Ye, Jianmei; Zhu, Yimeng; Huang, Dawei; Zhao, Xin (Frontiers in Psychiatry, 2023)
While studies indicate that high self-control may serve as a safeguard against problematic internet use, there's evidence suggesting that problematic internet use can, in turn, diminish self-control. This study aimed to elucidate the longitudinal interplay between internet self-control and problematic internet use in adolescents, employing cross-lagged panel modeling. Furthermore, drawing from a positive psychology perspective, we examined the potential role of 'meaning in life' as a protective mediator within this longitudinal relationship. We then constructed a mediation model to explore protective factors against problematic internet use. Through a questionnaire, we tracked 659 adolescents (331 males and 328 females; mean age=13.61) in a longitudinal design across two time points, spaced at five-month intervals, to assess their internet self-control, problematic internet use, and meaning in life. Results of the cross-lagged panel models showed that: Internet self-control had a significant negative impact on problematic internet use after five months (β= -0.094, p < 0.01).Conversely, problematic internet use had a significant negative impact on internet self-control after five months (β= -0.099, p < 0.05). Results from the longitudinal mediation model showed that: Meaning in life mediated the effect of internet self-control on problematic internet use after five months (βinternet self-control(T1)-meaning in life(T2) = 0.142, p < 0.01; βmeaning in life(T1)-problematic internet use (T2) = -0.075, p < 0.05). Our study uncovers a reciprocal predictive relationship between internet self-control and problematic internet use, while highlighting the mediating role of meaning in life within this relationship. These findings suggest that fostering internet self-control and cultivating a sense of meaning in life among adolescents can serve as effective prevention and intervention strategies for addressing the issue of problematic internet use.